a) | 6 x - 3 | = 9
b) | 3 x - 5 | = | 7 x - 10 |
Răspunsuri la întrebare
Răspuns de
1
a)|6x-3|=9
6x-3=9 sau 6x-3=-9
6x=9+3 6x=-9+3
6x=12 6x=-6
x=2 x=-1
6x-3=9 sau 6x-3=-9
6x=9+3 6x=-9+3
6x=12 6x=-6
x=2 x=-1
Răspuns de
0
A)MODUL 6X-3=9
⇒6X-3=9⇒6X=12⇒X=12:6⇒X=2
⇒6X-3=-9⇒6X=-9+3⇒6X=-6⇒X=-1
X∈(2,-1)
B)MODUL 3X-7=7X-10
⇒3X-7=7X-10⇒3X-7X=7-10⇒-4X= -3⇒ X=3/4
-(-3X-7)=-(-7X-10)
+3X+7=+7X+10
3X-7X=7+10=-4X=17⇒X= -17/4
⇒6X-3=9⇒6X=12⇒X=12:6⇒X=2
⇒6X-3=-9⇒6X=-9+3⇒6X=-6⇒X=-1
X∈(2,-1)
B)MODUL 3X-7=7X-10
⇒3X-7=7X-10⇒3X-7X=7-10⇒-4X= -3⇒ X=3/4
-(-3X-7)=-(-7X-10)
+3X+7=+7X+10
3X-7X=7+10=-4X=17⇒X= -17/4
Alte întrebări interesante
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Geografie,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă